MAKNA PERNIKAHAN DALAM PERSPEKTIF TASAWUF - Anisyah Anisyah (UIN Sunan Kalijaga Yogyakarta, 2020)
This article reviews the view of Sufism on marriage. Marriage is one of the human alternatives to fulfill biological needs and is one of the factors why marriage is highly recommended and celibacy is not recommended. Marriage is also a way for someone to be as close to God as possible. Therefore, it is very relevant if the problem of marriage is seen in the perspective of Sufism and applies the values of Sufism in human life as a provision for someone to build a household ark that is sakinah mawwadah and wa rohmah.